Liberalizing foodgrains markets: Experience, impacts and lessons from South Asia - Ganesh-Kumar, Anand; Roy, Devesh; Gulati, Ashok (Oxford University Press, 2010)
This volume examines the changing nature of policies regarding the foodgrains market in the post-liberalization period in South Asia. The volume explores the impact these policy changes have on food security, prices, production, consumption, and trade of foodgrains. Views from India, Bangladesh, Nepal, Pakistan, and Sri Lanka are discussed.